SURVEI TINGKAT KEBUGARAN JASMANI (VO2MAX) PADA MAHASISWA PRODI PENDIDIKAN OLAHRAGA UMKT - Nor Hidayatullah, Muhammad; Julianur (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
Physical fitness particularly aerobic capacity as reflected VO₂Max is a crucial component for sports education students as prospective professionals in the fields of coaching and physical education. This study aimed to determine the physical fitness level (VO₂Max) of students in the Sports Education Study Program at the University of Muhammadiyah East Kalimantan (UMKT). The study used a survey method with the Multistage Fitness Test (Beep Test) technique. The sample consisted of 14 male students selected through purposive sampling. Data analysis used descriptive statistics in the form of mean, standard deviation, frequency, and fitness category. The results showed that the average VO₂Max of students was in the